PSYCHOLOGY OF CHARACTERS IN ASMA NADIA’S NOVEL CINTA 2 KODI (SIGMUND FREUDS THEORY) - Hetilaniar; Zaleha, Eni; Agustina, Juaidah (Universitas PGRI Palembang, 2022)
The problem in this study is how is the literary psychology of the character in the novel cinta 2 KODI by Asma Nadia. The purpose of this study is to find out and analyze the literary psychology in the novel Cinta 2 KODI by Asma Nadia. The method used in this study is descriptive qualitative method. Data collection techniques use documentation tecniques.